Development of specific competencies in gymnastics in specialized higher education - Valeriu Jurat; Carolina Moga; Maria-Florica Grigore; Ion Carp; Marius-Viorel Ulăreanu; Roxana-Ștefania Drăgan; Daniela-Corina Popescu; Miroslawa Cieslicka (Physical Education of Students)
Background and Study Aim. The modernization of the curriculum in higher education, through its importance and significance, aims to ensure optimal conditions in the creation and continuous improvement of the personality of the student/future teachers of physical education. The purpose of the study was the comparative analysis of the academic programs for development of specific competencies in the specialized higher education.